EXPERIMENTALLY INDUCED CHRONIC AFLATOXICOSIS IN LAYING CHICKS (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to examine and describe the clinicopathological aspects of experimentally-induced chronic aflatoxicosis in laying one-day-old-Bovan chicks and to assess the efficacy of antimycotoxins and garlic (Allium sativum) in amelioration of its toxic effects. Five groups (A, B, C, D and E) of 20 one-day-old chicks were used in this experiment. Group A received a ration containing 90 ppb aflatoxins, group B received the same ration plus 10 mg ground garlic/ml daily, group C received the same ration plus Hydrated Sodium Calcium Alaminosilicate (HSCAS) at 1gm/kg, group D received a ration with 103 ppb aflatoxins, group E received a ration with 24.6 ppb aflatoxins and served as control. The experiment continued for 100 days, during which, the chicks were weighed weekly. At the end of this priod the chicks were killed for further investigations. Chicks in group A, B, C and D showed emaciation and pronounce loss of weight. Dullness, ataxia, paralysis of the legs and wings, gasping and complete recumbence were evident in group A and D. At necropsy, the livers of group A, B and D were fragile, pale with areas of haemorrhages and congestion. Histopathologically, group A and D displayed hepatocytes hydropic degeneration, infiltration of mononuclear cells predominantly lymphocytes which occasionally formed lymphoid follicles, bile duct proliferation  and haemorrhage which was more prominent in sub-capsular areas. Kupffer cells proliferation was evident only in group B and C. whereas, periportal fibrosis was shown in group D only. Group D had the highest aflatoxins residues in the livers (58.824%), followed by group A, B and C respectively. Group E showed no aflatoxins residues in the livers. The study demonstrated the inefficiency of garlic and the commercial Hydrated Sodium Calcium Alaminosilicate (HSCAS) in ameliorating the toxic effects of aflatoxins